PENGARUH METODE ROLE PLAYING DALAM MENGATASI BULLYING TERHADAP MINAT BELAJAR PJOK SISWA KELAS IV SDN 165 PALEMBANG - Ayu Wandira; Endie Riyoko; Endang Surtiyoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Role Playing method in addressing Bullying on students' interest in learning Physical Education (PJOK) among fourth-grade students at SDN 165 Palembang. The research method used was a Quasi-Experimental Design with a Nonequivalent Control Group design. The population in this study consisted of all fourth-grade students at SDN 165 Palembang. The sampling technique used was random sampling, resulting in class IV A as the experimental group and class IV B as the control group. Data collection techniques in this study included validated Bullying and PJOK learning interest questionnaires. Based on the hypothesis test results, the obtained t-values were 3.426 and 3.043, while the critical t-value (t-table) was 2.011. Since the t-values were greater than the critical t-value (t > t-table), the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Therefore, it can be concluded that there is a significant effect of the Role Playing method in addressing Bullying on students' interest in learning PJOK among fourth-grade students at SDN 165 Palembang.